Do Physician Assistant Training Programs Adequately Prepare PAs to Address Nutritional Issues in Clinical Practice?. Issue 2 (June 2022) - Wolf, Corri; Mandel, Ellen; Peniuta, Morgan; Lazure, Patrice; Smith, Noël E.; Peterson, Eric D.; Péloquin, Sophie
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to determine physician assistants' (PAs') current level of confidence to engage in nutrition-related tasks and their satisfaction with the nutrition education they received in PA school. Methods: To achieve this goal, a mixed-methods approach that consisted of 3 data collection phases (qualitative online discussions, quantitative survey, and qualitative interviews) was used to explore and measure PAs' perceptions of the education they received in PA school and through other sources and how confident they felt addressing nutrition-related issues in clinical practice. Results: While 80% of PAs endorse the idea that PAs should be more involved in providing nutritional care to patients, the majority reported basic or no knowledge of the nutritional implications of chronic conditions (69%), inflammatory bowel disease (69%), nutritional needs over the lifespan (67%), and food allergies and intolerances (64%). Barriers to patient care included knowledge-related challenges when selecting lab tests based on patient profile (46%) and identifying needs based on various gastrointestinal diseases (67%) and when using diagnostic data to identify deficiencies (74%). Overall, 59% of PAs reported being slightly or very dissatisfied with the nutrition-related content in the curricula used to formally train PAs. Conclusions: The primary goal of every PA program is to prepare its graduates to be competent to enter clinical practice. Regarding nutrition, these data indicate that programs are failing to do so. PAs lack the confidence and ability to provide optimal nutritional care, which is staggering considering that nutrition is the first line of treatment in the prevention and management of numerous chronic diseases.